Prognostic impact of BCL2, BCL6 and MYC status in de novo diffuse large B-cell lymphoma: a regional study of 43 patients - Kahraman, Dudu Solakoglu; Diniz, Gulden; Ceylan, Cengiz; Ozalp, Faruk Recep; Koca, Yetkin; Ekmekci, Sumeyye; Ayaz, Duygu; Sayhan, Sevil (International Journal of Research in Medical Sciences, 2019)
Background: Diffuse large B-cell lymphoma (DLBCL) is an aggressive non-Hodgkin lymphoma with marked biologic heterogeneity. We aimed to evaluate the status of MYC, BCL2, BCL6 in patients with DLBCL. Methods: Herein, we have investigated the prognostic relevance of MYC, BCL2 and BCL6 from 43 de novo DLBCL patients. Results: In this study, protein overexpression of BCL2 and BCL6 was encountered in 46.5% (n=20) and 27.9% (n=12) of the tumors, respectively. Rearrangements in MYC, BCL6, and BCL2 were detected in 9.3% (n=4), 25.6% (n=11), and 4.7% (n=2) of the cases, respectively. Any statistically significant difference could not be found between Bcl-2, Bcl-6 expression, C-MYC rearrangement and the survival. Conclusions: We concluded that C-MYC and BCL2 may contribute to aggressive transformation, so more mechanism-based therapy should be explored. A larger study is warranted to better understand the immunophenotypic and molecular features of DLBCL and their respective impact on patient survival.